Social Networks in Batik Enterpreneurs in Kampung Batik Laweyan Surakarta - Revi Qodri Arswinda; Nurhadi Nurhadi; Saifuddin Zuhri (Syntax Literate, 2023)
Batik, which is an icon of Surakarta City, Central Java Province, is one of the categories of Micro, Small, and Medium Enterprises (MSMEs) that has the potential to be developed. The Surakarta City Government inaugurated Kampung Batik Laweyan to become a batik MSME center, providing a platform for batik entrepreneurs to promote their products. Social capital in the form of networks is a component that needs to be developed by batik entrepreneurs. This study aims to describe the formation of social networks in batik entrepreneurs, the use of social networks, and actors who play a dominant role in batik business in Kampung Batik Laweyan. This descriptive qualitative research is analyzed using the theory of social capital. The components of social capital analyzed are networks, norms, and trust. The research results are; 1) Batik entrepreneurs in Kampung Batik Laweyan already have social networks with raw material suppliers and tailors who are categorized in micro social networks; 2) Batik entrepreneurs in Laweyan Batik Village have a social network with the Laweyan Batik Village Development Forum (FPKBL), private companies, banks and schools which are categorized in the meso social network; 3) Batik entrepreneurs in Kampung Batik Laweyan have social networks with the government that is categorized in macro social networks; 4) Utilization of social networks has not run optimally; 5) some actors play a dominant role in the running of the batik business in Kampung Batik Laweyan.